Análisis Financiero a las Compañías Comerciales de la provincia de Loja - González Sarango, Sandra Elizabeth (2023)
Financial analysis has become a support tool for those in charge of monitoring the fulfillment of institutional objectives, because it allows the evaluation of results of one or several accounting periods, facilitating decision making. The objective of the study is to analyze the financial situation of commercial companies in the province of Loja, period 2019-2021, through the application of financial indicators, in order to issue a criterion about the financial conditions in which the organizations under study operate. The research has a mixed approach, of exploratory and descriptive type, where the bibliographic technique was used and worked with a population of 10 commercial companies in the province of Loja. The main findings of the research reveal that during the period 2019-2020 the entities increased their revenues, assets and liabilities, which resulted in a 19.94% increase in profits. For the period 2020-2021 a decrease of 31.94 % is evidenced, however, profit generation is maintained. In accordance with the evaluation for the year 2021, the results obtained in the financial indicators verified adequate levels of liquidity, solvency, profitability and efficient management. In all indicators, they managed to remain above the standard value and the national average. Therefore, it can be concluded that the commercial companies in the province of Loja were able to adapt to the changes and overcome the mobility barriers derived from the health crisis. In order to raise the level of knowledge of the partners of the commercial companies, a financial analysis guide was created to provide basic information on the process of obtaining information used in decision-making.